D-Dimer Concentrations and COVID-19 Severity: A Systematic Review and Meta-Analysis - Paliogiannis, Panagiotis; Mangoni, Arduino Aleksander; Dettori, Paola; Nasrallah, Gheyath K.; Pintus, Gianfranco; Zinellu, Angelo (Frontiers in Public Health, 2020)
Coronavirus disease 2019 (COVID-19) is a recently described infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Since late 2019, COVID-19 has rapidly spread in virtually all countries, imposing the adoption of significant lockdown and social distancing measures. The activation of the coagulation cascade is a common feature of disseminated intravascular coagulation and adverse clinical outcomes in COVID-19 patients. In this study, we conducted a meta-analysis aiming to investigate differences in serum D-dimer concentrations in patients with and without severe COVID-19 disease. An electronic search in Medline (PubMed), Scopus and Web of Science was performed with no language restrictions, and 13 articles were reporting on 1,807 patients (585, 32.4% with severe disease) were finally identified and included in the meta-analysis. The pooled results of all studies revealed that the D-dimer concentrations were significantly higher in patients with more severe COVID-19 (SMD: 0.91mg/L; 95% CI, 0.75 to 1.07 mg/L, p<0.0001). The heterogeneity was moderate (I2=46.5%; p=0.033). Sensitivity analysis showed that the effect size was not modified when any single study was in turn removed (effect size range, 0.87 mg/L to 0.93 mg/l, Figure 3). The Begg’s (p=0.76) and Egger’s tests (p=0.38) showed no publication bias. In conclusion, our systematic review and meta-analysis showed that serum D-dimer concentrations in patients with severe COVID-19 are significantly higher when compared to those with non-severe forms.